Synthesis Metal-Organic Framework (MOFs) Cr-PTC-HIna Modulated Isonicotinic Acid for Methylene Blue Photocatalytic Degradation - Adawiah Adawiah; Wulandari Oktavia; Nanda Saridewi; Farhan Maulana Azhar; Risma Nur Fitria; Muhammad Shofyan Gunawan; Sri Komala; Agustino Zulys (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2022)
A novel responsive visible light Cr-based MOF, Cr-PTC-HIna, was synthesized using the solvothermal method. Cr-PTC-HIna peaks were observed at 2θ = 9.04°, 12.71°, 14.88°, 25,48°, 27.72°, 28.97°, and 43.60° with a crystal size of 21 nm. Band gap energy achieved from the Cr-PTC HIna was 2.05 eV. Scanning Electron Microscope (SEM) analysis obtained a 3D structural morphology of MOFs Cr-PTC-HIna with a cylindrical tube shape and a particle size of 251.45 nm. Cr-PTC-HIna gave the optimum methylene blue degradation at pH of 7 under 250 watts mercury lamp irradiation for 180 minutes with degradation capacity of 95.40 mg/g. Electron holes and hydroxyl radicals were found as the dominant species contributing to methylene blue degradation. Copyright © 2022 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).